Comparative Characteristics of Mucous Membrane of Various Parts of Rectum Of Rat - Boymurodova Mehriniso Nurmurodovna (International Journal on Orange Technologies, 2021)
It was found that the formation of the components of the mucous membrane of the rat anal canal occurs in different ways, depending on the age and division. By the 6th day, an increase in the thickness of the epithelial cover of the transition zone prevails. In the pre-sphincter section, by the 6th month, an increase in the thickness of the submucosa is expressed